Development IT Adoption Method for E-learning in Merged University - Rima Aditya, Bayu; Handoko Wijoyo, Mary (School of Applied Science, Telkom University, 2017)
This research presents an overview to develop an IT adoption method for e-learning in a Merged University. The development of IT adoption method in the Merged University is done by adjusting the gap between three elements: IT maturity level (in this case IT for elearning), category adopter of each Merged University and IT adoption criteria of individual actors of adoption. The maturity level of IT maturity level refers to Gartner, Hype Cycle, and Priority Matrix. Classification groups refer to adopter categories according to Rogers. The adoption model uses UTAUT model. For the process, a priority calculation method utilizes Analytical Hierarchy Process (AHP). IT adoption method for e-learning in a Merged University has been tested and can be applied Telkom University, formed from four universities.